Analisis Preferensi Masyarakat Desa Ngasem Dalam Mengambil Pembiayaan Antara Bank “Plecit” Dan Lembaga Keuangan Syariah - Zahwa Naelal Firdausi; Ahmad Fauzan Mubarok (VALUE, 2024)
This research aims to analyze the preferences of the people of Ngasem Village in choosing sources of financing between Bank "Plecit" and sharia financial institutions. The research method uses a qualitative approach through interviews to understand the factors that influence these preferences, including accessibility, familiarity and practicality. The research results show that the majority of Ngasem Village residents tend to choose Bank "Plecit" because of ease of access, fast processing and familiarity, even though the interest rates are high. "Plecit" Bank is considered to have an attractive marketing strategy, especially for MSMEs and housewives, despite its unethical billing practices. Islamic financial institutions need to improve attractive marketing strategies to compete with Bank "Plecit" and expand public understanding of Islamic finance. Socialization efforts, expanding access, simplifying procedures and providing more attractive incentives are needed to increase public preference for Islamic financial institutions. For the importance of expanding public understanding of sharia financial institutions and promoting ethical values ​​in financing. so that it can increase public preference for sharia financial institutions.